Addressing Multicultural Misconceptions: A Study at Muhammadiyah Higher Education Institutions - Sri Roviana; Masduki, Yusron; Yusutria, Yusutria; Ahmad Sunawari Long (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This study explores the comprehension of students from Muhammadiyah higher education institutions concerning Indonesia's multiculturalism and its distinct ethnic, religious, racial, and intergroup diversities, termed SARA, esteemed as national assets. Design/methods/approach – Utilizing a qualitative approach, data was assimilated from a literature review, focused group discussions (FGD) of [specific number, if available], comprehensive observations at Ahmad Dahlan University in Yogyakarta, in-depth interviews with purposively selected informants, and examination of pertinent documents. Findings – Preliminary findings suggest an underdeveloped understanding of multiculturalism among the students, frequently leading to misconceptions. Rather than being viewed as an inclusive concept, multiculturalism is often perceived as threatening to certain religious adherents. Specifically, minority sects like Shia and Ahmadiyya are perceived with apprehension. This knowledge gap can be attributed to limited discourse by UAD lecturers, predominantly homogeneous student interactions, and a lack of engagement with multicultural literature. Research implications – The observations from this research underscore the need to enhance SARA-oriented educational strategies at higher learning institutions. Implementing comprehensive multicultural education can pave the way for mutual respect and appreciation of SARA diversity, especially within Muhammadiyah Higher Education Institutions (PTM). Notably, the research's scope is restricted to Ahmad Dahlan University, Yogyakarta, which might not necessarily represent other Muhammadiyah academic environments.